Developing Russia–NATO relations: problemsof arms control and limitations on destabilizing military activities of the Alliance - I. Kuznetsov (Международная аналитика, 2016)
The article is devoted to some critical aspects of correspondence of the Alliance status to the basic norms of international law. It also centers on specific actual steps of the realization of the NATO long-term strategy of «openness» in interrelations with the existing universal and regional institutionalized regimes of limitations in the sphere of international security and arms control. Special attention is paid to the NATO strategy of abstention from the direct participation in critical processes of negotiations in the sphere of arms control and limitations on destabilizing military activities. The NATO, as an organization of permanent nature, stands for the position of non-responsibility for the compliance of obligations in this sphere by its member-states. Decomposition of these artificial obstacles is an unavoidable condition for the NATO responsible inclusions in processes of arms control and reduction of large-scale military activities within the OCSE competence.